Masquerade Syndrome: Retinoblastoma presenting as Sympathetic Ophthalmia - Khalid Iqbal Talpur, Sajjad Ali Surhio, Noor Bakht Nizamani (Pakistan Journal of Ophthalmology, 2018)
Purpose: Masquerade syndromes are a group of ocular diseases that may mimic chronic intraocular inflammation, they may be benign or malignant. We report a case of retinoblastoma presenting as sympathetic ophthalmia: malignant uveitic masquerade syndrome. Material and Methods: A 6 year old female presented with trauma in the right eye following which she developed uveitis in the left eye two months later. She was diagnosed as a case of sympathetic ophthalmia and enucleation of right eye was done. The histopathology suggested it was a retinoblastoma (RB). Since the child’s history was not suggestive of RB and her age was old for RB we requested the laboratory to review the slides again. A board of pathologists reviewed the slides, concluding that it was a RB undoubtedly. Result: Based on this, she was diagnosed as a case of malignant uveitic masquerade syndrome. Patient was referred to advance oncology unit for further management of RB. Conclusion: Refractory uveitis in a young child should be thoroughly evaluated for malignant uveitic masquerade syndromes.